TRANSFORMATION PROCESSES IMPLEMENTED IN THE BANKING SYSTEM AND POSSIBILITIES OF IMPLEMENTING IT IN OUR COUNTRY - Suyunov Dilmurod Kholmuradovich; Ergashev Khusan; Ergashev Mirzabek (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: This study aims to analyze the New Uzbekistan Development Strategy for 2022-2026, which seeks to make the digital economy the main driver of economic growth by increasing its volume by at least 2.5 times. Additionally, it examines the strategy’s goal of completing the transformation of state-owned commercial banks and increasing the share of private banks in total bank assets to 60% by the end of 2026. Method: The research involves an in-depth analysis of the modernization processes in the banking sector, focusing on mutual trust and transparency between banks and clients. It also reviews global practices and the impact of scientific and technological progress on banking activities. Results: Findings indicate that the rapid adoption of advanced technological solutions is essential for the modernization of the banking system. Furthermore, increasing transparency and trust between banks and customers is a key factor in achieving sustainable growth. The study also highlights the potential challenges in balancing state-owned and private banking sector contributions. Novelty: This study provides a comprehensive evaluation of the role of digital transformation in banking modernization within the framework of Uzbekistan's development strategy. It offers new insights into the factors influencing financial sector reforms and the impact of scientific and technological advancements on banking efficiency.